Spray pyrolysis-assisted synthesis of hollow cobalt nitrogen-doped carbon catalyst for the performance enhancement of membraneless fuel cells - Ji, Jungyeon; Kyungmin Yim; An, Heeyeon; Yoo, Sung Jong; Chung, Yongjin; Kim, Jinsoo; Kwon, Yongchai (John Wiley & Sons Inc., 2022)
Hollow cobalt nitrogen-doped carbon (H-CoNC) is suggested for use in the membraneless hydrogen peroxide fuel cell (HPFC) and enzymatic biofuel cell (EBC) as anodic catalyst boosting hydrogen peroxide oxidation reaction (HPOR). For fabricating H-CoNCs, a facile spray pyrolysis-assisted process is used, and such produced H-CoNCs show a porous and hollow-shell structure, while they include a large amount of isolated Co atoms and coordinate bonds with Co and nitrogen (Co-N-4). This structure promotes mass transfer to the active site and excellent catalytic activity for HPOR. With these benefits of H-CoNCs, the current density of the bioanode consisting of H-CoNC, carbon nanotube, and glucose oxidase (H-CoNC/CNT/GOx) observed at 0.3 V under 150 mM glucose is 315.5 mu A cm(-2), which is 2.1 times higher than that of a conventionally synthesized catalyst using Co-doped carbon nanoparticles (CoNC-NPs) (CoNC-NPs/CNT/GOx, 146.2 mu A cm(-2)). With this superior catalytic activity for HPOR, maximum power density (MPD) of membraneless EBC using H-CoNC/CNT/GOx is 33.8 +/- 4.52 mu W cm(-2), which is 52% higher than that of CoNP-NPs/CNT/GOx. In addition, a membraneless HPFC using H-CoNC/CNT demonstrates 4.87 times higher MPD (231.3 +/- 11.3 mu W cm(-2)) than that using CoNC-NPs/CNT, proving that H-CoNC improves the performance of fuel cells by its excellent catalytic activity.